1996
DOI: 10.1046/j.1365-2125.1996.35418.x
|View full text |Cite
|
Sign up to set email alerts
|

CYP1A2 activity, gender and smoking, as variables influencing the toxicity of caffeine

Abstract: We have investigated several factors that might be related to the occurrence of toxic effects during the performance of a urinary test with caffeine (300 mg p.o), in 120 healthy volunteers. A total of 218 toxic effects were self-reported by eightytwo (68%) subjects. Females and nonsmokers were at the highest risk (chi-square test, P=0.01). Furthermore, two nonsmoking females experienced a symptomatology with delirium, restlessness, muscle tremor, vomiting and wakefulness. Among females and nonsmokers, those su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
44
0
6

Year Published

1997
1997
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(52 citation statements)
references
References 10 publications
2
44
0
6
Order By: Relevance
“…It has consistently been demonstrated that females on average have a lower CYP1A2 activity than males. For example, females have higher drug concentrations than males both of the probe drug caeine [18] and of psychotropic CYP1A2 substrates such as clozapine [19] and olanzapine [20]. In contrast, females might have a somewhat higher CYP2D6 activity than males, although the dierence is negligible or close to negligible [21].…”
Section: Discussionmentioning
confidence: 88%
“…It has consistently been demonstrated that females on average have a lower CYP1A2 activity than males. For example, females have higher drug concentrations than males both of the probe drug caeine [18] and of psychotropic CYP1A2 substrates such as clozapine [19] and olanzapine [20]. In contrast, females might have a somewhat higher CYP2D6 activity than males, although the dierence is negligible or close to negligible [21].…”
Section: Discussionmentioning
confidence: 88%
“…In addition, in vitro CYP1A2 activity towards phenacetin O-deethylation was observed here to be lower within the Chinese female samples than the Chinese male samples, but such a gender difference was not significant with the Caucasian samples. In earlier human studies, CYP1A2 activity towards caffeine metabolism appeared to be lower for women than men in Chinese [26] and Caucasians [27].…”
Section: Discussionmentioning
confidence: 99%
“…Females were not included due to gender differences in caffeine consumption and metabolism (Carrillo and Benitez, 1996;Magkos and Kavouras, 2005). The study was approved by the medical ethical committee at Maastricht University academic hospital.…”
Section: Participantsmentioning
confidence: 99%